(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article investigates the effectiveness of the Suggestopedia method among EFL language learners. This teaching approach combines Suggestopedia’s calming methods, like relaxation and mental imagery, with interactive digital resources to foster a dynamic learning experience.